Multifunctional Adaptive System for Physiotherapy with Measurement Devices - Dimitrov, D. Tz.; Guergov, S.; Ralev, N. D. (Elektronika ir Elektrotechnika, 2010)
An investigation on structure of one multifunctional adaptive system for physiotherapy with measurement devices has been done in the paper. In the paper there are descriptions of different parts of the multifunctional system. Some characteristics and properties of different units of multifunctional system have been done, also. Some possibilities for simultaneously applications of different system’s units are described, also. It’s important to provide simultaneously application of different system’s units only when their physiological influences on the human body are compatible. Simultaneously application of magneto-therapy, mechanical acupressure and cranial electro stimulation or ionophoresis is described in the paper.